P-569 Reduction of gonadotropin-dosage towards the end of ovarian stimulation for IVF/ICSI improves ART-outcome in a subgroup of patients. (30th June 2022) - Lawrenz, B; Melado, L; Del Gallego, R; Loja, R; Coughlan, C; Ruiz, F; Fatemi, H
Abstract: Study question: To identify in an unselected patient population those patients, who would benefit from a gonadotropin stepdown towards the end of ovarian stimulation in IVF/ICSI-treatment Summary answer: Reduction of gonadotropin-dosage during ovarian stimulation for IVF/ICSI is beneficial in FSH-stimulated patients, aged 26-30 years, and in HMG-stimulated patients, aged 36-40 years of age What is known already: Ovarian stimulation with gonadotropins for multi-follicular growth is a crucial part of IVF/ICSI-treatment. Intensive administration of gonadotropins might lead to progesterone elevation (PE) in the late follicular phase, impacting negatively the endometrial receptivity and possibly the embryo quality. During follicular growth, the number of FSH- and LH-receptors shift from predominantly FSH-receptors in the early to predominantly LH-receptors in the late follicular phase, reducing susceptibility of the follicle towards systemic FSH-levels. In a good prognosis population, it was shown that lower systemic FSH-levels on the trigger-day lead to significantly lower progesterone levels without reducing the number of retrieved/mature oocytes. Study design, size, duration: Retrospective analysis of 1276 ovarian stimulation cycles, performed as GnRH (Gonadotropin-Releasing-Hormone)-antagonist protocol in an unselected patient population, between January 2018 and December 2020 at ART Fertility Clinic, Abu Dhabi, UAE. Ovarian stimulation cycles were split according to the stimulation medication used (either only recombinant FSH (rFSH) or only human menopausal gonadotropin (HP-HMG)) and whether stimulation-dosage was reduced (reduction group, RG) during the stimulation course or not (non-RG). Furthermore, patients were stratified into age-groups. Participants/materials, setting, methods: Couples with primary / secondary infertility and an indication for ovarian stimulation for IVF/ICSI were included, independent of their age or ovarian reserve parameters. Only GnRH antagonist cycles, with either rFSH or HP-HMG as sole medication for ovarian stimulation and available data on Antral Follicle Count (AFC), gonadotropin-dosage at stimulation-start and -end, oocyte yield (number of retrieved / mature) and hormonal parameters of estradiol, progesterone and FSH were included. Main results and the role of chance: A total of 1276 ovarian stimulation cycles were included, 495 (38.79%) with rFSH and 781 (61.21%) with HP-HMG as stimulation medication. In the FSH-group, 295 patients reduced (reduction-group=RG) and 200 did not reduce (=non-RG) FSH-dosage during stimulation. In all age-categories (<25; 26-≤30; 31-≤35; 36-≤40; 41-45years), FSH-end-dosage was significantly lower in the RGs compared to the non-RGs (p < 0.001, respectively). Despite not significantly different patient characteristics (AFC, BMI (Body Mass Index), mean age, FSH-starting dosage), in patients aged 26-≤30years, a significantly higher number of oocytes (retrieved/mature) were obtained in the RG (16.0±7.1 vs 20.4±8.3;p<0.001 / 12.6±6.5 vs 15.8±7.0;p=0.004, respectively) without an increase in progesterone-levels (1.0±1.3 vs 0.9±0.6ng/ml;p=0.95). The HP-HMG group was composed of 437 patients in the RG and 344 patients in the non-RG-group. In all age-categories (<25; 26-≤30; 31-≤35; 36-≤40; 41-52years), HP-HMG-end-dosage was significantly lower in the RGs (p < 0.001, respectively). The age-group 36-≤40 showed no significant differences in AFC, BMI, age and HP-HMG-starting-dosage, and still, a significantly higher number of oocytes (retrieved/mature) were obtained in the RG-group (7.2±5.61 vs 9.8±6.13;p<0.001 / 5.7±4.7 vs 7.8±5.0;p<0.001, respectively). The progesterone-levels on trigger day in the nRG-group was 0.5±0.3ng/ml and 0.6±0.4ng/ml in the RG group, which is significantly different (p < 0.001), however, clinically insignificant. Limitations, reasons for caution: The retrospective design is a limitation to this study as well as the exclusion of ovarian stimulation cycles, which were cancelled and no oocyte pick-up procedure was performed. Furthermore, in some age-categories, patients in RG and non-RG were different regarding their basic characteristics. Wider implications of the findings: This analysis demonstrates, that in specific patient populations, gonadotropin-dosage can be reduced without impacting the oocyte yield and preventing progesterone-elevation despite higher oocyte yield. Furthermore, reduction of gonadotropins towards the end of the follicular phase results in a more physiologic course of the gonadotropin-levels during ovarian stimulation. Trial registration number: not applicable